Nutritional evaluation of former food products (ex-food) intended for pig nutrition. Issue 8 (3rd August 2017) - Giromini, C.; Ottoboni, M.; Tretola, M.; Marchis, D.; Gottardo, D.; Caprarulo, V.; Baldi, A.; Pinotti, L.
ABSTRACT: Ex-food or former food products (FFPs) have been proposed as one of the categories with great promise as alternative feed ingredients. FFPs' nutritional potential is not yet fully exploited. Therefore, the aim of this study was to perform a nutritional evaluation of selected FFPs. In particular, six samples of mixed FFPs, all based on bakery products, were analysed for moisture, crude protein, ether extract, crude fibre, neutral detergent fibre, acid detergent fibre, starch and ash. Nitrogen-free extractives and non-structural carbohydrate were also determined. Based on FFPs' composition data, estimation of digestible energy and metabolisable energy values for pigs were calculated. Further, the in vitro digestibility values of FFPs were investigated using a multi-step enzymatic technique. A wheat sample was included as a control feed ingredient in the study. All data were reported on dry matter basis. FFPs have shown a nutrient composition comparable with cereal grains. In the tested FFPs, the average protein content was 10.0% and the average starch content was 52.4%. Nitrogen-free extractive ranged from 61.2% to 74.7%, whereas non-structural carbohydrate ranged from 58.5% to 79.3%. Compared with wheat, FFPs were characterised by a relative high fat content, averaging about 10.1%. The relatively high nitrogen-free extractive/non-structural carbohydrate/starch and fat concentration designated FFPs as valuable energy sources. Digestible energy and metabolisable energy averages were 17.2 and 16.9 MJ kg –1, respectively. The average in vitro digestibility value of FFPs samples was 88.2% ± 5.8%, comparable with that of wheat (90.6% ± 1.6%). FFPs are a fat-fortified version of common cereals grains. The high energy content and digestibility values elect FFPs as promising non-traditional ingredients for swine.